Minocycline treatment in clinically isolated syndrome and serum NfL, GFAP, and metalloproteinase levels. (November 2022) - Camara-Lemarroy, Carlos; Metz, Luanne; Kuhle, Jens; Leppert, David; Willemse, Eline; Li, David KB; Traboulsee, Anthony; Greenfield, Jamie; Cerchiaro, Graziela; Silva, Claudia; Yong, V Wee
Background: In the trial of Minocycline in Clinically Isolated Syndrome (MinoCIS), minocycline significantly reduced the risk of conversion to clinically definite multiple sclerosis (CDMS). Neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAP) are emerging biomarkers in MS, and minocycline modulates matrix metalloproteinases (MMPs). Objective: To assess the value of blood NfL and GFAP as a biomarker of baseline and future disease activity and its utility to monitor treatment response in minocycline-treated patients with clinically isolated syndrome (CIS). Methods: We measured NfL, GFAP, and MMPs in blood samples from 96 patients with CIS from the MinoCIS study and compared biomarkers with clinical and radiologic characteristics and outcome. Results: At baseline, NfL levels correlated with T2 lesion load and number of gadolinium-enhancing lesions. Baseline NfL levels predicted conversion into CDMS at month 6. GFAP levels at baseline were correlated with T2 lesion volume. Minocycline treatment significantly increased NfL levels at 3 months but not at 6 months, and decreased GFAP levels at month 6. Minocycline decreased MMP-7 concentrations at month 1. Discussion: Blood NfL levels are associated with measures of disease activity in CIS and have prognostic value. Minocycline increased NfL levels at month 3, but reduced GFAP and MMP-7 levels.